PEMETAAN KEMATIAN AKIBAT COVID-19 BERDASARKAN VARIABEL EPIDEMIOLOGI - Adu, Apris; Mas’amah, Mas’amah (JURNAL KAJIAN VETERINER, 2021)
There are plenty of determinants of the increase of death rates in Indonesia such as old age diseases, and poor access to health facilities. The increase in death rates has impacted Indonesians both economically and also their mental health. The purpose of this study is to map the COVID-19 death cases, using an epidemiological point of view. A sample size of 179 deceased persons due to COVID-19. This study was done from June to August 2021 using medical and interview data and was analyzed using a descriptive approach. The results show that Bakunase community health center has the largest death cases with 42 cases, while W.Z. Yohanes Hospital is the hospital with the most death cases at 50 cases. 116 deceased persons were male, and most of them were aged more than 60 years old (n = 90). Diabetes Mellitus was the most common comorbid disease (27%). This study has mapped the death rates of COVID-19 in Kupang and the implications were discussed further within.